Cathepsin B promotes the progression of pancreatic ductal adenocarcinoma in mice. Issue 6 (9th December 2011) - Gopinathan, Aarthi; DeNicola, Gina M; Frese, Kristopher K; Cook, Natalie; Karreth, Florian A; Mayerle, Julia; Lerch, Markus M; Reinheckel, Thomas; Tuveson, David A
Abstract : Objective: The lysosomal protease cathepsin B is upregulated in human pancreatic ductal adenocarcinoma (PDA) and represents a potential therapeutic target. Loss of cathepsin B delays tumour progression in mouse models of islet, mammary and intestinal carcinoma and decreases invasion and metastasis. This study examines the role of cathepsin B in the initiation, progression and metastasis of PDA. Methods: Cathepsin B germline knockout mice were crossed with animals expressing an endogenous Kras G12D allele in the pancreas, and mice were aged to evaluate the role of cathepsin B in pancreatic intraepithelial neoplasia (PanIN). A survival study was also performed with mice carrying an additional heterozygous conditional Trp53 R172H allele. Cell lines derived from tumours were used to investigate the role of cathepsin B in vitro, and subcutaneous allografts investigated the cell autonomous and non-cell autonomous roles of cathepsin B in pancreatic cancer. Results: Constitutive cathepsin B loss resulted in delayed progression of both PanIN and PDA and a significant survival advantage in mice. Cathepsin B-deficient PDA cells and PanIN showed decreased proliferation and mitogen-activated protein (MAP) kinase signalling. The reconstitution of deficient cells with cathepsin B reversed these findings, which correlated with decreased levels of the active forms of the related protease cathepsin L. Conversely, acute ablation of cathepsin L activated the MAP kinase cascade in PDA cells. Conclusions: These results confirm that cathepsin B plays an important cell autonomous role in the progression of PDA and suggest that the regulation of cathepsin L by cathepsin B may be a means of stimulating cell proliferation in neoplasia.